Liposomes as Carriers of GHK-Cu Tripeptide for Cosmetic Application - Michał Dymek; Karolina Olechowska; Katarzyna Hąc-Wydro; Elżbieta Sikora (MDPI AG, 2023)
Liposomes are self-assembled spherical systems composed of amphiphilic phospholipids. They can be used as carriers of both hydrophobic and hydrophilic substances, such as the anti-aging and wound-healing copper-binding peptide, GHK-Cu (glycyl-L-histidyl-L-lysine). Anionic (AL) and cationic (CL) hydrogenated lecithin-based liposomes were obtained as GHK-Cu skin delivery systems using the thin-film hydration method combined with freeze-thaw cycles and the extrusion process. The influence of total lipid content, lipid composition and GHK-Cu concentration on the physicochemical properties of liposomes was studied. The lipid bilayer fluidity and the peptide encapsulation efficiency (EE) were also determined. Moreover, in vitro assays of tyrosinase and elastase inhibition were performed. Stable GHK-Cu-loaded liposome systems of small sizes (approx. 100 nm) were obtained. The bilayer fluidity was higher in the case of cationic liposomes. As the best carriers, 25 mg/cm3 CL and AL hydrated with 0.5 mg/cm3 GHK-Cu were selected with EE of 31.7 ± 0.9% and 20.0 ± 2.8%, respectively. The obtained results confirmed that the liposomes can be used as carriers for biomimetic peptides such as copper-binding peptide and that the GHK-Cu did not significantly affect the tyrosinase activity but led to 48.90 ± 2.50% elastase inhibition, thus reducing the rate of elastin degeneration and supporting the structural integrity of the skin.